2016
DOI: 10.1007/s10853-016-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic degradation of a phenolic compounds’ mixture using a highly efficient TiO2/reduced graphene oxide nanocomposite

Abstract: A nanocomposite (namely rGOTi) was prepared by loading 0.33 weight percent of reduced graphene oxide (rGO) on commercial TiO 2 nanoparticles using a hydrothermal method. The as-prepared nanocomposite was characterized using surface and bulk analytical techniques such as X-ray photoelectron spectroscopy, X-ray diffraction, and Fourier transform infrared and Raman spectroscopies. Also, the surface area was measured using the Brunauer-EmmettTeller technique. In addition, the UV-Vis diffuse reflectance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Further experiments focused on changing the applied pressure during the filtration process of 5 mL of different solutions of rhodamine B and phenol red at different concentrations of 5, 10, and 20 ppm, using a membrane filter (Figure 4a,b). It is worth mentioning that the choice of the concentrations (20 and 10 ppm) was based on the concentrations reported in the literature [7,17,[19][20][21]. A high vacuum (i.e., low pressure and high suction power) enhanced the removal of the dyes in all cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further experiments focused on changing the applied pressure during the filtration process of 5 mL of different solutions of rhodamine B and phenol red at different concentrations of 5, 10, and 20 ppm, using a membrane filter (Figure 4a,b). It is worth mentioning that the choice of the concentrations (20 and 10 ppm) was based on the concentrations reported in the literature [7,17,[19][20][21]. A high vacuum (i.e., low pressure and high suction power) enhanced the removal of the dyes in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…Filtration can be achieved using different types of cellulose filter papers and microporous membranes [1,9,[13][14][15][16][17][18]. Among the commonly used membranes are nylon membranes [7,17,[19][20][21] which will be used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…15 H. Al-Kandari shown that the band gap energy for TiO 2 was lowered from 3.11 to 2.96 eV when it was composited with rGO to form the rGOTi. 16 Cuprous oxide (Cu 2 O) is a promising low-cost, narrow bandgap material in visible-light photocatalytic eld. As a typical metal-decient p-type semiconductor with a bandgap between 2.0-2.2 eV, the spectral absorptance of the naturally occurring copper oxide has a bulge at 600 nm and a plateau that falls off at about 700-800 nm, so Cu 2 O can absorb most of the visible light and the theoretical photoelectric conversion efficiency can reach 18%.…”
Section: Introductionmentioning
confidence: 99%
“…4a) show diffraction patterns of both anatase and rutile phases. The peaks located at 25.4, 37.9, 48.0, 54.0, 55.1, 62.8, 69.1, 70.5 and 75.2° were assigned to the anatase phase (JPDS 21–1272), whereas the peaks assigned to the rutile phase were obtained at 27.5, 36.1 and 41.1° (JPDS 21–1276) 23, 44 . Figure 4e shows two distinctive diffraction peaks: a strong peak located 27.4° with an interlayer spacing of 3.2 Å and a broad peak located at 13.1° with an interlayer spacing of 6.8 Å, which can be indexed to the hexagonal phase of graphitic C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…These studies included changing the experimental conditions and synthesis methods of TiO 2 913 , metal particle loading 5, 6, 14 and using a co-catalyst 5, 6, 15 . Considerable attention has been focused on utilizing carbonaceous nanomaterials as a support for TiO 2 to improve its photocatalytic performance due to their unique electrical properties and controllable structures 7, 1623 . An example of these supports is graphitic carbon nitride (g-C 3 N 4 ), which can be obtained from the pyrolysis of nitrogen-rich organic precursors and is considered the most stable allotrope of carbon nitride 14 .…”
Section: Introductionmentioning
confidence: 99%